Na stráži samoděržaví. Vladimir Andrejevič Gringmut a Ruská monarchistická strana, 1905–1907 - Zbyněk Vydra (Theatrum Historiae)
The Russian Monarchist Party was one of the first Russian rightist parties. It was established in April 1905 as a response on the revolution and on the tsarist Manifesto of 18th February. The party was founded and headed by Vladimir Andreevich Gringmut (1851–1907), ultra-conservative journalist and editor of the Moscow newspapers Moskovskiia Vedomosti. Gringmut spoked for an unlimited tsarist autocracy and refused any form of parliamentarism. His ideology was based on the principles of „orthodoxy, autocracy and nationality“. Anti-semitism, anti-liberalism, adoration of strong state power and criticism of Western influences in the Russian life was characteristical for Gringmut and its party. After Nicholas II announced the new State Duma with legislative power on 17th October 1905, Gringmut had to change his opinion and the Russian Monarchist Party took part in the Duma elections. It was not successful in the first (1906) and second (1907) elections, same as the other rightist parties. Only after the election law was changed in June 1907, the rightist parties gained more votes and became an important faction in the State Duma. But the Russian Monarchist Party was only marginally successful. It made a substantial impact in and around Moscow, but never gained an all-Russian influence. Contrary to the limited party’s importance, Gringmut was the leading spirit of the monarchist movement in Russia during the revolution. His activity was enormous, he participated on the All-Russian Monarchist Congresses and tried to unite the rightist parties in one all-Russian organization, nonetheless without success. Gringmut died in September 1907, when the rightist movement culminated. After his death, Russian Monarchist Party was in a steady decline.